2007
DOI: 10.1111/j.1526-4610.2007.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Preference for Migraine Preventive Therapy

Abstract: Patients' preference regarding migraine prevention is very important in headache management. Patients rated efficacy the most important aspect in preventive therapy and preferred treatment options with higher efficacy rates. Future studies are needed for a better understanding of patients' preference for migraine prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 11 publications
(11 reference statements)
7
90
1
1
Order By: Relevance
“…Most commonly prescribed prophylactic medications in Spanish prevention studies are topiramate, amitriptyline, propranolol and flunarizine [22], a similar finding to our study. However, a study performed in a headache center from an urban Brazilian population reported the frequent use of vitamins/herbal therapies (24%), and non-medicinal therapy (32%) to prevent migraine [23]. Frequent use of non-pharmacological measures in the Brazilian population suggests an under-utilization of efficacious preventive drugs.…”
Section: Discussionmentioning
confidence: 97%
“…Most commonly prescribed prophylactic medications in Spanish prevention studies are topiramate, amitriptyline, propranolol and flunarizine [22], a similar finding to our study. However, a study performed in a headache center from an urban Brazilian population reported the frequent use of vitamins/herbal therapies (24%), and non-medicinal therapy (32%) to prevent migraine [23]. Frequent use of non-pharmacological measures in the Brazilian population suggests an under-utilization of efficacious preventive drugs.…”
Section: Discussionmentioning
confidence: 97%
“…Comments: The choice of 50% or greater reduction is arbitrary yet clinically relevant as most patients with migraine value 50% improvement in headache frequency as the most important attribute of an effective migraine preventive drug (131).…”
Section: Responder Ratementioning
confidence: 99%
“…It is well understood that patients who suffer from migraine are burdened by factoring in considerations to accommodate impending migraine attacks. The disruptions to work, family, and social activities caused by migraine translate into an overall poorer quality of life 13, 20. In this study, patients who had at least 1 month of 100% response had more freedom from their migraine headaches across the 6‐month dosing period.…”
Section: Discussionmentioning
confidence: 99%